Modelling and design of grid voltage oriented vector control scheme for DC railway recuperating system - Toh C.L.; Tan C.W. (Institute of Advanced Engineering and Science, 2024)
The braking energy harvested by a railway vehicle can be restored to the utility grid with a power recuperating system. A grid connected voltage source inverter (VSI) is commonly used as a grid-feeding converter in the recuperating system. This paper proposes to integrate grid voltage oriented vector control (GVOVC) and third harmonic voltage injection pulse width modulation (THVI-PWM) technique for the VSI to ensure grid voltage and frequency synchronization. A simulation study is carried out to evaluate the feasibility of the proposed control and modulation schemes using MATLAB/Simulink. The results show that the proposed controller may reach steady-state operating mode within 7 ms by producing good quality AC voltages and currents waveforms. With the independent control of voltage quantities in dq reference frame, the regulation of active and reactive power could be realized. 2023 Institute of Advanced Engineering and Science. All rights reserved.